Worksheet Based on POE: Media Development on Acid Base - Wijayadi, Andri Wahyu; Noer Af’idah; Oktaffi Arinna Manasikana (Indonesian Journal of Mathematics and Natural Science Education, 2023)
This research aims to develop acid base worksheet based on POE and find out their validity and readability to support chemistry lessons. This development research uses the 4D models. The research consists of three steps, define, design, and development. The research subject consisted of two experts and 15 students. Research data collection techniques used expert validation questionnaires and student response questionnaires with a Likert scale of 1 - 4. The results of the study were analyzed quantitatively showing that the worksheets that had been developed met the validity requirements with very valid criteria in terms of material experts and learning design experts with a percentage average 96.06% and 95.51%. Student responses to the product show that the product is very suitable for use in learning based on an average percentage of 91.35%. This means that acid base worksheet based on POE can be one of the teaching materials for chemistry lessons.